The Influence of pile batter angle, soil unit weight and soil moisture content on the ultimate axial tensile load capacity of micropiles - Du Toit, Francois (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.